Ich sehe was, was du nicht siehst: Eine Eye-Tracking-Studie zur Betrachtung und Bewertung von Bildern aus der Schweinemast; I Spy with my Little Eye: An Eye-tracking Study regarding the Perception and Evaluation of Pictures from Pig Fattening Barns - Gesa Busch; Sarah Arianna Gauly; Achim Spiller (German Journal of Agricultural Economics (GJAE), 2017)
– In order to correct romantic ideas about livestock farming in society and to provoke acceptance of husbandry systems, there is a recent trend in the agricultural industry towards using real pictures of barns for communication purposes. Up to now there are only few studies investigating how these pictures are perceived. The current study examines how these pictures from pig fattening barns are looked at and how they are evaluated by students (without and with connection to agriculture; in the following named as citizens and farmers) to derive recommendations for the choice of pictures. Therefore, a survey is combined with eye-tracking. Pictures of a pen with fully slatted floor are evaluated negatively by citizens and different pictures of the same pen influence the evaluation. This is not the case for farmers who evaluate the pictures in a more neutral manner. However, the eye movements of farmers and citizens when viewing the pictures are very similar in general. Independent of the picture, the face regions and bodies of the animals are always viewed at first. Furthermore, we show that citizens do not recognize toys in a barn and unattractive or common pictures are viewed less. First recommendations for choosing pictures for public relations in agriculture can be drawn from the results.
Keywords: 330